2021
DOI: 10.3748/wjg.v27.i44.7705
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive 333 base pair interleukin 10 receptor alpha subunit deletion in very early-onset inflammatory bowel disease

Abstract: BACKGROUND Interleukin 10 receptor alpha subunit (IL10RA) dysfunction is the main cause of very early-onset inflammatory bowel disease (VEO-IBD) in East Asians. AIM To identify disease-causing gene mutations in four patients with VEO-IBD and verify functional changes related to the disease-causing mutations. METHODS From May 2016 to September 2020, four young patients with clinically diagnosed VEO-IBD were recruited. Before hospitalization, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…333-bp deletion in IL10RA was recognized to contribute to four cases of clinically diagnosed VEO-IBD with inconclusive IL10RA mutations. Most importantly, they confirmed that typical clinical manifestations and increased serum levels of IL-10 strongly indicate the existence of IL-10R dysfunction [237]. GWASs have additionally documented common polymorphisms in the IL-10 pathway as risk factors for IBD in adults [238].…”
Section: Interleukin 10mentioning
confidence: 67%
See 1 more Smart Citation
“…333-bp deletion in IL10RA was recognized to contribute to four cases of clinically diagnosed VEO-IBD with inconclusive IL10RA mutations. Most importantly, they confirmed that typical clinical manifestations and increased serum levels of IL-10 strongly indicate the existence of IL-10R dysfunction [237]. GWASs have additionally documented common polymorphisms in the IL-10 pathway as risk factors for IBD in adults [238].…”
Section: Interleukin 10mentioning
confidence: 67%
“…IL-22 is a member of the IL-10 family and is produced by Th-17 cells, γδ T cells, and newly described innate lymphoid cells (ILCs) [248]. IL-22 is crucial for maintaining intestinal epithelial homeostasis and barrier function, providing protective effects in IBD [237]. IL-22 and IL-18 serve crucial functions in the delicate cytokine balance that determines host defense and inflammation particularly at biological barriers.…”
Section: Interleukin 22mentioning
confidence: 99%
“…[ 53 ] Notably, although our data mainly come from European populations, previous studies have found that IL-10RA dysfunction is a major cause of very early-onset IBD (VEO-IBD) in East Asian populations, where a potential mechanism might be a novel 333-bp deletion in IL10RA. [ 54 ] Mentioning this aims to highlight the importance of genetic background in IBD onset and the potential differences among various populations. Furthermore, it suggests that future research should more broadly explore the diversity of IBD pathogenesis mechanisms across different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%